Perforation of the appendix and the sigmoid colon by an ectopic IUD - Ayodele, Atolagbe O.; Oloruntobi, Rahaman M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The perforation of both appendix and sigmoid colon by an ectopic Intrauterine device (IUD) by an intrauterine device is a rare occurrence. We present a case of a patient is a 47- year- old hispanic woman who presented at the Gynaecology clinic with complaints of chronic right sided pelvic pain. She had an intrauterine device inserted 10 years prior with no recent gynaecological follow-up. The device was identified by ultrasonography and she was planned for a hysterectomy and IUD retrieval by the gynaecology team. An intra-operative finding of sigmoid colon and appendiceal perforation by an IUD during a total abdominal hysterectomy and emergent involvement of the general surgery team. She underwent a segmental resection of the involved sigmoid colon, appendectomy and removal of the IUD. All missing Intrauterine devices should be accurately localized by tomographic or magnetic imaging preoperatively.